Risk factors associated with progressive myelomalacia in dogs with complete sensorimotor loss following intervertebral disc extrusion: a retrospective case-control study - Castel, Aude (BMC Vet Res, 2019)
BACKGROUND: Progressive myelomalacia (PMM) is a usually fatal complication of acute intervertebral disc extrusion (IVDE) in dogs but its risk factors are poorly understood. The objective of this retrospective case-control study was to identify risk factors for PMM by comparing dogs with complete sensorimotor loss following IVDE that did and did not develop the disease after surgery. We also investigated whether any risk factors for PMM influenced return of ambulation. Medical records of client-owned dogs with paraplegia and loss of pain perception that underwent surgery for IVDE from 1998 to 2016, were reviewed. Dogs were categorized as PMM yes or no based on clinical progression or histopathology. Walking outcome at 6 months was established. Signalment, onset and duration of signs (categorized), steroids, non-steroidal anti-inflammatory drugs (yes or no), site of IVDE (lumbar intumescence or thoracolumbar) and longitudinal extent of IVDE were retrieved and their associations with PMM and walking outcome were examined using logistic regression. RESULTS: One hundred and ninety seven dogs were included, 45 with and 152 without PMM. A 6-month-outcome was available in 178 dogs (all 45 PMM dogs and 133 control dogs); 86 recovered walking (all in the control group). Disc extrusions at the lumbar intumescence were associated with PMM (p = 0.01, OR: 3.02, CI: 1.3–7.2). Surgery performed more than 12 h after loss of ambulation was associated with PMM (OR = 3.4; CI = 1.1–10.5, p = 0.03 for 12-24 h and OR = 4.6; CI = 1.3–16.6, p = 0.02 for the > 24 h categories when compared with the ≤12 h category). Treatment with corticosteroids was negatively associated with PMM (OR: 3.1; CI: 1.3–7.6, p = 0.01). The only variable to affect walking outcome was longitudinal extent of IVDE (OR = 2.6; CI = 1.3–5.3, p = 0.006). CONCLUSION: Dogs with lumbar intumescence IVDE are at increased risk of PMM. Timing of surgery and corticosteroid use warrant further investigations. PMM and recovery of walking are influenced by different factors.